Level of Satisfaction of Fishermen Against Service of Capture Operational Needs at the Sibolga Archipelago Fisheries Port, Central Tapanuli Regency, North Sumatra Province - Silvina Winta; Alit Hindri Yani; Usman Usman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACKThis research was conducted in April 2019 at the Sibolga Archipelago Fisheries Port (PPN), Central Tapanuli Regency, North Sumatra Province. This study aims to obtain the value of the level of satisfaction of service and the level of performance of service operational needs of the capture of Sibolga VAT. Data collection was carried out at the Sibolga Archipelago Fisheries Port (PPN), Central Tapanuli Regency, North Sumatra Province. The method used in this study is the survey method. All data obtained were processed using CSI and IPA analysis. The fisherman satisfaction index value on the service attributes of fuel, water and ice needs is considered to have satisfied the fishermen and is important for fishermen who are in the scale range of 0.61 to 0.80 with the numbers 0.76, 0.80 and 0.77. And the service needs of the pier, TPI, and basket in Sibolga PPN are considered to be very satisfying for fishermen and very important for fishermen who are in the scale range of 0.81-1.00 indicated by the numbers 0.83, 0.83, and 0.84. Keywords: Fishermen Satisfaction, Service, Arrest Operations